(untitled) (Sains Humanika, 2015)
This study aimed to examine forgiveness among university students in term of gender and age.Â In this quantitative study, a sample taken from 500 of undergraduate and postgraduate Malaysian university students of 240 males and 260 females with three range of ages 20-29 (younger adult), 30-39 (middle adult) and 40 years above (older adult). Data were analyzed by using Rasch Model for psychometric properties of the Heartland Forgiveness scale. Independent t-test and one way ANOVA were used to analyze the differences in gender and age of the students on forgiveness. In term of psychometric properties results showed that person reliability (0.77) and item reliability (1.00) indicate that students involved in this study were reliable and items used were highly reliable. Result presented that there was no significant difference on forgiveness for both gender and age of the university students. It was recommend that forgiveness should be explored to other factors related to it such as anger, religiosity, health, culture, background of respondents and other factors in the context of Malaysian perspective. In order to help individuals reap the benefits associated with forgiveness and avoid the consequences associated with unforgiveness, educational systems in university suggested focusing on providing students with the moral perspective closely related to the subjects about forgiveness in the syllabus of their study.